2020
DOI: 10.26822/iejee.2020562139
|View full text |Cite
|
Sign up to set email alerts
|

ICT-Driven Writing and Motor Skills: A Review

Abstract: The development of writing skills is recognized as a mandatory process for initial education and the foundation of all essential learning. Writing skills are crucial to children's socialization and interaction with their environment as they grow. The development of writing skills has been linked to a complex set of key factors, but is not yet clear enough. In the context of 21st-century education, and to increase understanding of this phenomenon, a systematic literature review of 40 years of published studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Según los datos, en los años 2021-2023 se publicó el mayor número de trabajos científicos relevantes para la enseñanza de la preescritura en educación inicial. Esta investigación explora y analiza las numerosas publicaciones que los países han realizado sobre el tema de la enseñanza de la preescritura para niños (Patiño et al, 2020). Según Alemu (2020), los procesos de preescritura y escritura son cruciales para el desarrollo y el éxito de un individuo en su vida social y profesional, los cuales dependen en gran medida de que padres y docentes trabajen juntos para crear oportunidades para que los niños crezcan y se desarrollen en el ambiente escolar y en casa.…”
Section: Discussionunclassified
“…Según los datos, en los años 2021-2023 se publicó el mayor número de trabajos científicos relevantes para la enseñanza de la preescritura en educación inicial. Esta investigación explora y analiza las numerosas publicaciones que los países han realizado sobre el tema de la enseñanza de la preescritura para niños (Patiño et al, 2020). Según Alemu (2020), los procesos de preescritura y escritura son cruciales para el desarrollo y el éxito de un individuo en su vida social y profesional, los cuales dependen en gran medida de que padres y docentes trabajen juntos para crear oportunidades para que los niños crezcan y se desarrollen en el ambiente escolar y en casa.…”
Section: Discussionunclassified
“…In addition, it is stated that the time required to write a letter varies according to the shape and size of the letter, and since the shapes of some letters are easier to produce because they are simple, the writing time of each letter is not equal (Güneş, 2016). Writing is a skill that requires gross and fine motor skills and should be supported in early childhood through play-based learning environments and lessons such as physical education (Patiño et al 2020).In addition to these, it can be said that the method used to measure the writing speed (dictation or copying) is one of the factors that causes differences in writing speed.…”
Section: Limitations Of the Research And Future Directionsmentioning
confidence: 99%
“…Patiño, Calixto, Chiappe and Almenarez ( 2020) justify that the pervasive incorporation of Information and Communication Technologies (ICT) in writing assists primary ESL learners to build words, acquire a lexicon and collectively create coherent sentences and texts. With the current existence of salient technology, several studies on ICT in the subject of writing have reported that there is a proliferation in the usage of blog and online diaries among teenagers (Patiño et al, 2020;Yüce, 2020). Mansouri (2017) also highlights that blog writing as a form of Internet-based resource, acts as a genuine and motivating learning tool in many educational contexts, especially within primary ESL classrooms.…”
Section: Emphasis On Writing Skillsmentioning
confidence: 99%